2013
DOI: 10.1002/14651858.cd004434.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor antagonists for pulmonary arterial hypertension

Abstract: Endothelin receptor antagonists can increase exercise capacity, improve WHO/NYHA functional class, prevent WHO/NYHA functional class deterioration, reduce dyspnoea and improve cardiopulmonary haemodynamic variables in patients with pulmonary arterial hypertension with WHO/NYHA functional class II and III. However, there was only a trend towards endothelin receptor antagonists reducing mortality in patients with pulmonary arterial hypertension. Efficacy data are strongest in those with idiopathic pulmonary hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…At this moment several endothelin receptor blockers are available for clinical use, but their indication is restricted to the treatment of pulmonary hypertension and digital ulcers related to systemic sclerosis [34][35][36][37]. Endothelin receptor blockade in patients who develop hypertension during antiangiogenic treatment is an attractive option, knowing that aberrant activation of the endothelin axis may also underlie the progression of various solid tumors, including ovarian, prostate, colon, breast, bladder, and lung cancers [38 & ].…”
Section: Implications For the Clinicmentioning
confidence: 99%
“…At this moment several endothelin receptor blockers are available for clinical use, but their indication is restricted to the treatment of pulmonary hypertension and digital ulcers related to systemic sclerosis [34][35][36][37]. Endothelin receptor blockade in patients who develop hypertension during antiangiogenic treatment is an attractive option, knowing that aberrant activation of the endothelin axis may also underlie the progression of various solid tumors, including ovarian, prostate, colon, breast, bladder, and lung cancers [38 & ].…”
Section: Implications For the Clinicmentioning
confidence: 99%
“…Bosentan is a dual endothelin‐A and endothelin‐B receptor antagonist used to treat patients with idiopathic PAH . There are only limited experiences using endothelin receptor antagonists (ERAs) in patients with PoPH as patients are often excluded from randomised controlled clinical trials in PAH.…”
Section: Transplantation For Patients With Pophmentioning
confidence: 93%
“…Two separate receptors of ET have been identified: type A receptors, which induce vasoconstriction by increasing intracellular calcium, most commonly found on vascular SMCs; and type B receptors, located on endothelial cells, stimulate the release of vasodilating agents, such as nitric oxide and prostacyclin. Theoretically, either selective blocking of ET type A receptors alone or nonselective blocking of both ET type A and ET type B receptors together has vasodilating functions as a result of relaxation of vascular SMCs [17]. Evidence suggested that ET was overexpressed in the lungs of patients with PAH and elevated plasma ET concentrations were associated with poor prognosis [18].…”
Section: Et-1mentioning
confidence: 99%
“…ET receptor antagonists are a new class of drugs for the treatment of many diseases, including PAH. ET receptor antagonists are potent vasodilators and antimitotic substances, which could specifically dilate and remodel the pulmonary artery, and have recently been proposed as an alternative therapy [17]. ET receptor antagonists have become the mainstays of the treatment of PAH.…”
Section: Et-1mentioning
confidence: 99%